PENGARUH PEMIKRAN POLITIK HASAN AL-BANNA DALAM PARTAI KEADILAN SEJAHTERA PASCA REFORMASI DI INDONESIA TAHUN 1998-2014 - ", Priandoko; ", Muchid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Religion as worldview has contributed few main roles on world politics constellation for decades. One of them is Hasan Al Bana’s political thoughts, “Manhaj Harokah”. This research analyzes the influence of Hasan al-Banna—the founder of Ikhwanul Muslimin—political thoughts in Indonesia. This research is aimed to describe how Indonesia through “Partai Keadilan Sejahtera” adopt Hasan al-Banna’s thoughts on politics and governance. Formulation of Hasan al-Banna’s thoughts and vision about Islam and governance that has been adopted and absorbed in Indonesia will be explained based on Political Thought Theoretical Framework. These qualitative-descriptive research framework formulates ideology, actor, value system infiltration, institution, and political movement as one theoretical unity. Which means that, Hasan al-Banna’s thoughts focus on these four research concepts. The result of this research shows that Hasan al-Banna’s political thoughts influence Indonesia political situation by the existence of “Partai Keadilan Sejahtera” as the da’wah-based party. PKS is Indonesian’s manifesto on adopting Hasan al-Banna’s thoughts. The establishment of PKS is one of two main influences on Indonesia political situation. And another one is Islam purification, getting back to “quran and hadits”. Some previous researcher also called PKS establishment as the rise of “Jemaah Tarbiyah” in Indonesia. Keywords: Hasan al-Banna, tarbiyah, dakwah, PKS